Large-scale evacuation : the analysis, modeling, and management of emergency relocation from hazardous areas /: the analysis, modeling, and management of emergency relocation from hazardous areas. (2019) - Lindell, Michael K; Murray-Tuite, Pamela M (Pamela Marie), 1975-; Lindell, Michael K; Wolshon, P. Brian (Paul Brian); Baker, Earl J
No abstract available